2020
DOI: 10.1021/acs.jafc.0c05389
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Approaches to Decipher the Binding Mechanism of General Odorant-Binding Protein 2 from Athetis lepigone to Chlorpyrifos and Phoxim

Abstract: Insect resistance to insecticides is an increasingly serious problem, and the resistant mechanisms are complicated. The resistance research based on the chemosensory pathway is one of the hot problems at present, but the specific binding mechanism of chemosensory genes and insecticides remains elusive. The binding mechanism of AlepGOBP2 (belong to insect chemosensory gene) with two insecticides was investigated by computational and experimental approaches. Our calculation results indicated that four key residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…In accordance with previous methods, 21,37–39 purified PCR products of AlepOBP6 were first subcloned into the pEASY ‐ Blunt3 cloning vector (TransGen). The expression vectors pET‐30a(+) (Novagen) and pEASY‐Blunt3‐AlepOBP6 plasmid were then digested using FastDigest® restriction enzymes BamHI and XhoI (Fermentas), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with previous methods, 21,37–39 purified PCR products of AlepOBP6 were first subcloned into the pEASY ‐ Blunt3 cloning vector (TransGen). The expression vectors pET‐30a(+) (Novagen) and pEASY‐Blunt3‐AlepOBP6 plasmid were then digested using FastDigest® restriction enzymes BamHI and XhoI (Fermentas), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A Spectra Max M2 fluorescence spectrophotometer (Molecular Devices) was used for the fluorescence competitive binding assays, as previously described 37,38,40 . At the beginning, the fluorescent probe N ‐phenyl‐1‐naphthylamine (1‐NPN) and ligand (sex pheromones and maize volatiles) were dissolved in chromatography‐grade methanol to give a 1 m m solution.…”
Section: Methodsmentioning
confidence: 99%
“…53 In several previous studies, the two odorants have been found to strongly bind olfactory-related proteins including GOBPs. 18,19,54,55 In Athetis lepigone, AlepGOBP2 exhibited a high affinity to chlorpyrifos, of which its two sites (Phe12 and Ile94) were of particular importance in the binding of this insecticide, but not including Ile52 and Phe118. 19 Our analysis on the PxutGOBP1 mutation from Phe118 to Ala showed a similar result with the mutated AlepGOBP2 Phe118Ala , i.e., they exhibited a slightly reduced binding affinity to chlorpyrifos.…”
Section: Discussionmentioning
confidence: 99%
“…The optimized structure was fully dissolved in a rectangular water box filled with TIP3P (size 10.0 Å × 14.5 Å × 10.0 Å) [35,36]. The RSFF2C force field was applied for MD calculation [37]. All systems were equilibrated by NVT and NPT for 500 ps [29,38].…”
Section: Molecular Dynamics (Md) Simulationmentioning
confidence: 99%